Evaluation of Acid-Base Status and some Serum Biochemical Parameters in Male Nubian Goat Kids as Influenced by Dietary Supplementation with Molasses - Elkhair, Nawal M.; Adam, Osman, A. O. (Journal of Veterinary Medicine and Animal Production, 2021)
The objective of the study was to evaluate acid-base status and some serum biochemical parameters in male Nubian goat kids as influenced by dietary supplementation with molasses. Twenty clinically healthy male Nubian goat kids (age: 4-6 months; weight 9-11kg) were used. The kids were assigned into 4 groups receiving different levels of molasses: 0% (M-0), 30% (M-30), 40% (M-40) and 45% (M-45) for a period of 5 weeks. Blood samples were collected from the jugular vein weekly and were used for the determination of blood pH, some serum electrolytes (Na+, K+ and Cl-), serum total protein and albumin. The values of acid-base parameters: strong ion difference (SID3), the concentration of total non-volatile weak acids (A tot-protein and A tot-albumin) were calculated using the equations:serum-[SID3] = [Na+] + ([K+] - [Cl-], serum-[Atot-protein]=[Protein](g/dl)´3.6 and serum-[Atot-albumin]=[Albumin](g/dl)´7.6, respectively. A significant (P<0.01) increase in feed intake and body weight gain was observed in supplemented kids after 3-4 weeks. Serum- [Na+], [K+], [Cl-] and total protein (TP) increased significantly (P≤0.05) in response to dietary supplementation; however, only TP was affected significantly (P≤0.05) by the duration of dietary supplementation with molasses. The initial mean values of blood pH, serum-[SID3], serum-[A tot-protein] and serum-[A tot-albumin] were 7.3-7.4,45-54 mmol/l, 21-23 mmol/l and 24-27 mmol/l, respectively. Dietary supplementation with molasses had no significant effect on blood pH except for the group supplemented M-45. Serum- [SID3], [A tot-protein] and [A tot-albumin] fluctuated during the experimental period; however, this pattern of response was not statistically significant except for serum-[SID3] in week one. As a conclusion, molasses at a level of 30-40%up to 3 weeks improve growth performance of Nubian goat kids with no significant effect on acid-base and electrolytes status. The duration of dietary supplementation with molasses had a significant impact on acid-base status, electrolytes and serum proteins concentration.